SME’s Access to Islamic financing for Enhancing Energy Efficiency: A Fuzzy AHP approach - Nurfadilah, Dety; Noer Rahmi, Asri; Febryanti, Shavira; Dinta Insyani Zukhruf Firdausi, Ratu (Bina Nusantara University, 2025)
Energy efficiency remains a significant challenge for Small and Medium Enterprises (SMEs) in Indonesia, contributing to high operational costs and limiting competitiveness. This research explored the key factors influencing SMEs' access to Islamic financing for energy efficiency. The study employs the Fuzzy Analytical Hierarchy Process (AHP), drawing on responses from 10 experts, including industry practitioners, academics, and regulators. Data were collected through focus group discussions, followed by additional interviews to validate and enrich the analysis. The findings indicate that financial health is the top priority criterion, followed by compliance with Islamic finance principles and management capabilities. The results highlight the importance of Islamic financial literacy and managerial skills in improving SMEs’ access to funding. Additionally, developing partnerships with Islamic financial institutions and implementing energy-efficient technologies are crucial strategies for enhancing financial sustainability. This research provides valuable insights for policymakers. Structured financial literacy programs and advisory centers should be introduced to help businesses navigate Islamic financing options. Policies should also promote the development of SME-friendly Islamic financial products to reduce risk perceptions. Furthermore, tax incentives, Green Sukuk, and low-cost refinancing options should be introduced to encourage energy-efficient investments. Clear regulatory guidelines and the integration of Shariah-compliant fintech solutions will help ensure compliance with these regulations. Ultimately, these efforts will contribute to reducing energy poverty and enhancing the competitiveness of SMEs in Indonesia.